Keanekaragaman Tumbuhan Tingkat Tinggi di Desa Tikonu Kecamatan Wundulako Kabupaten Kolaka - Agista Rahmadani; Selviana Selviana; Aswani Aswani; Shelvi Indriani; Fahiza Fahiza; Suci Regina Putri; Sulistiawati Mahsar; Rismawati Rismawati; Maretik Maretik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aimed to determine the diversity of higher plants in Tikonu Village, Wundulako District, Kolaka Regency. This was a quantitative descriptive study employing a survey method with a plot-transect technique across three observation stations within the plantation area. Each plot measured 10 m × 10 m. Data were analyzed using the Shannon-Wiener diversity index, relative abundance, evenness, and dominance. The results revealed the presence of 16 higher plant species, comprising a total of 70 individuals. The diversity index (H') values ​​for Stations I, II, and III were 1.47, 1.30, and 1.56, respectively, all falling within the moderate category. Evenness (E) values ​​ranged from 0.81 to 0.92, while dominance values ​​ranged from 0.25 to 0.32. The species exhibiting the highest relative abundance at each station were Cocos nucifera, Theobroma cacao, and Musa paradisiaca. The findings indicate that the plantation area in Tikonu Village possesses a moderate level of higher plant diversity, characterized by a relatively even distribution of individuals and a low level of dominance.